The Relationship Between Nurses' Attitudes and Motivation with Compliance The Use of Personal Protective Equipment at RSUD Ngimbang Lamongan - Sholihah, Iklimatus; Sari, Sheviana Puspita; Rohmatunnisak, Febi; Suratmi, Suratmi; Ubudiyah, Masunatul (STIKES Adi Husada, 2024)
Nurses in providing nursing care to patients must refer to the SOP that has been implemented by the hospital, including adherence to the use of Personal Protective Equipment (PPE) in treating patients with a positive attitude and high motivation. It is expected that a nurse has good behavior in using PPE. The purpose of this study was to determine the relationship between attitude and motivation for using personal protective equipment (PPE) at Ngimbangs Hospital. This study used a correlational analytic design with the cross-sectional method and used a random sampling technique to obtain 88 respondents. Research data was collected using a questionnaire consisting of a nurse’s attitude questionnaire, motivation scale, and compliance with the use of personal protective equipment (PPE) questionnaire. All questionnaires were declared valid and reliable. The results showed a positive attitude with high adherence of 46 nurses (53.3%). The data were analyzed using the Spearman rho test and obtained a value of p= 0.000 and a value of 0,516, meaning that there is a relationship between attitudes and adherence to the use of Personal Protective Equipment (PPE) in Ngimbang Hospital. The result showed the nurses who had high motivation and high compliance were 46 nurses (52.3%). The research data were analyzed using the Spearman rho test and obtained a value of p= 0.000 and a value of 0,508, maintaining the health and comfort of nurses in any type of work environment, especially in a hospital.